2010
DOI: 10.4028/www.scientific.net/amr.146-147.1243
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanism of Titanium on Cast Fluidity of ZG45

Abstract: The effects of titanium modification, which was added along with the pouring liquid in ladles, on the shrinkage porosity and cavity of cast steel ZG45 smelted in intermediate frequency induction furnace were studied. The metal liquid fluidity was measured by casting spiral samples. 0.2 wt.% titanium modification achieved the highest fluidity for steel liquid. Proper content of titanium could effectively increase the volume of concentrated shrinkage cavity, and restrain the forming of shrinkage porosity. By sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…With the addition of Ti in steel, previous works [14-16] have reported that it is indispensable that TiC will form which can be the effective heterogeneous nucleation of the matrix during solidification, thereby the solidified microstructure of the steel matrix was refined. During the heterogeneous nucleation process, an absorbed layer of the nucleated steel matrix is expected to be formed on TiC phase-dependent on their orientation relationships of disregistry.…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of Ti in steel, previous works [14-16] have reported that it is indispensable that TiC will form which can be the effective heterogeneous nucleation of the matrix during solidification, thereby the solidified microstructure of the steel matrix was refined. During the heterogeneous nucleation process, an absorbed layer of the nucleated steel matrix is expected to be formed on TiC phase-dependent on their orientation relationships of disregistry.…”
Section: Introductionmentioning
confidence: 99%